Microbiological quality analysis of grouper salted fish (Epinephelus Fuscoguttatus) in several traditional markets in ambon - Talakua, Gratia; Yunita, Melda; Husein, Anggun Lestary (JPBIO (Jurnal Pendidikan Biologi), 2024)
Salted fish is one of the food ingredients that is in demand by the community and has great potential in almost all traditional markets in Maluku, especially in the city of Ambon. One of the salted fish is grouper fish (Epinephelus fuscoguttatus) great potential, so it is necessary to conduct food safety checks from the microbiological aspect. This study aimed to analyze the total plate count of bacteria in grouper salted fish sold in several traditional markets in Ambon City, Indonesia. The research method used was quantitative descriptive with an experimental laboratory approach. The results of the total bacterial plate in the grouper salted fish sample from the Mardika market ranged from 1,55 x 103 CFU/mL to 1,05 x 104 CFU/mL, the origin of the Rumah Tiga market ranged from 3,85 x 103 to 3,5 x 104 and the origin of the Waiheru market ranged from 9,5 x 102 to 4,5 x 103 CFU/mL. In conclusion, the three samples of grouper salted fish do not exceed the maximum limit of the total plate count according to the Indonesian National Standard (INS) of 1x105 CFU/g so considered safe for consumption from a microbiological aspect.